The Influence of Glucose Exposure Load and Peritoneal Membrane Transport on Body Composition and Nutritional Status Changes after 1 Year on Peritoneal Dialysis. Issue 4 (July 2017) - Caron-Lienert, Rafaela Siviero; Poli-de-Figueiredo, Carlos Eduardo; Figueiredo, Ana Elizabeth Prado Lima; da Costa, Bartira Ercília Pinheiro; Crepaldi, Carlo; Pizzato, Alessandra Campani; Ferrari, Fiorenza; Giuliani, Anna; Ronco, Claudio
Background: The characteristics of peritoneal membrane transport differ among patients, affecting the prescription of peritoneal dialysis (PD) modality and glucose exposure in order to achieve an effective dialysis. This study aims to verify the influence of glucose exposure load and peritoneal membrane transport on body composition and nutritional status changes after the first year of PD. Methods: We examined a cohort of 85 incident PD patients during the first year of treatment. We established a cut-off of 5% to define changes in dry weight (DW), lean tissue mass (LTM), and fat mass (FM). Results: In total, 50.6% of the patients presented DW gain, 41.2% showed LTM loss, and 65.9% presented FM gain. Over the time (T0 – T12), we found significant differences in DW, body mass index (BMI), adipose tissue mass (ATM), FM and fat tissue index (FTI). Patients with lower dialysate-to-plasma creatinine ratio showed DW and FM gain. We observed a higher percentage of nonfast transporters in DW gain when comparing with DW no gain. As for glucose exposure load, no body composition changes were seen. Conclusions: Most patients presented DW gain, FM gain, and LTM loss. The characteristics of peritoneal membrane transport affected DW during the first year, changes being greater in nonfast than in fast transporters.